PENGARUH KECANDUAN PENGGUNAAN GAWAI TERHADAP HASIL BELAJAR MATEMATIKA - istanti, melly; Meifiani, Nely Indra (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2023)
Addiction to the use of gadgets can have an effect on student learning outcomes, even though gadgets themselves have sophistication that can support student learning processes. The purpose of this study was to determine whether there is an effect of gadget use addiction on mathematics learning outcomes. This research is a quantitative research with an ex post facto approach. The population in this study were class X students at SMK Negeri 1 Sudimoro and SMK Negeri Ngadirojo in the 2022/2023 student year. The instruments used in this study were a gadget use addiction questionnaire, a study concentration questionnaire, and documentation of students' midterm test results. The results of the data analysis concluded that devices had an effect of 54.1% on mathematics learning outcomes. Keywords- Gadget, study concentration, and learning outcomes